CONTEXTUALIZING THE REVELATION AS A COMMUNICATION PROCESS - Mochammad Irfan Achfandhy (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2020)
AbstractThe purpose of the descent of the Qur'an is to sustain human life on earth. So that the Qur'an is used as authentic sources in the teachings of Islam, including in interpreting the revelations. The concept of this revelation is an important theme in the discussion of Ulumul Qur'an and to this day still leaves plenty of room for creative and speculative thinking. Several stages and procedures for revelation still open the door to speculative thinking especially regarding the way of Allah and the angel Gabriel and communication with the Prophet Muhammad. All information that explains the existence of communication between Allah and the Angel Gabriel to the Prophet Muhammad. In this research, the study of revelation will be expanded and viewed from a communication perspective. So that the findings of this study can interpret revelation is a process of communication to the Prophet Muhammad.Keywords; al-Quran, revelation, communication